Changes in forest structure values along the natural cycle and different management strategies in Nothofagus antarctica forests - Martínez Pastur, Guillermo José; Rosas, Yamina Micaela; Chaves, Jimena Elizabeth; Cellini, Juan Manuel; Barrera, Marcelo Daniel; Favoretti Bondar, Santiago; Lencinas, María Vanessa; Peri, Pablo Luis (Forest Ecology and Management)
Ecologically sustainable forest management aims to preserve ecosystem integrity by providing wood and non-wood values. For this, it is necessary to determine the losses produced by the different management practices in natural forest resilience. The aim was to determine changes in forest structure values along the natural cycle and human impacts generated by rural timber, pastoral and silvopastoral uses in managed, unmanaged, and transformed Nothofagus antarctica forests of Tierra del Fuego (Argentina), as well as in some associated environments (grasslands). We sampled 145 sites to determine landscape characterization, microclimate, soil properties, debris, forest structure and regeneration under different conditions: (i) six phases of natural forest dynamic (even-and uneven-aged), (ii) four types of management and conversion alternatives with and without natural regeneration, and (iii) forest edges and grasslands. Main results showed that stand characteristics (abiotic, soil, forest structure, and regeneration) did not significantly change along the different natural forest phases in even- and uneven-aged structures. However, many studied variables strongly varied depending on harvesting intensities and fire occurrence. The magnitude of these changes was directly related to the impact degree. Multivariate analyses showed a close relationship among the different natural forest phases, and how stands with harvesting or different conversion intensity differ from the control stands, or how much they become similar to openlands. Through different indexes, we related the modifications of the stand characteristics with the magnitude and direction of the changes. Then, these could be used to propose sustainable forest management strategies in the framework of silvopastoral systems. Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Rosas, Yamina Micaela. Consejo Nacional de Investigaciones Científicas y ...